A crônica e seus diferentes estilos na obra de Humberto de Campos - Scheibe, Roberta (2006)
The present dissertation fulfills a study of the chronicles ( short stories ) collections written by Humberto de Campos, entitled Da seara de Booz (From the Fields of Booz) (1915), A serpente de bronze (A Bronze Snake) book signed with the pseudonym Conselheiro XX (Adviser XX) (1921), Sombras que sofrem (Suffering Shadows) (1934), and Últimas crônicas (The Last Chronicles) (1936). In this work, is investigated the presence of the political and social criticism, the humor and the irony, and a dramatic or confessional tone on these specific texts. Besides, it s possible to check the kind of chronicle that prevails in each one of the books, grounding this analysis on the proposed classification to this gender by Antonio Candido, Luiz Beltrão and Afrânio Coutinho. The research, that assumes an analytical method, results in a comparison between the books that form the corpus, when we are referring about subjects and styles